Critón. - Platón; Abecia Baldivieso, Valentín; Gisbert, Teresa; Mesa, José de (San José CR: EUCR, 1977)
Presenta uno de los escritos más importantes de Platón: Critón
Keywords: PLATON; FILOSOFIA; TEORIA